Boyer-Moore horspool algorithm used in content management system of data fast searching - Chan, Chung Hoong; M. A., Ameedeen (American Scientific Publishers, 2017)
After a deep view on few fast searching algorithm as Boyer-Moore algorithm, Boyer-Moore Horspool algorithm, Brute-Force Algorithm, Knuth-Morris-Pratt algorithm and Rabin-Karp algorithm, this research paper chooses Boyer-Moore Horspool algorithm to used in the content management system in term of data Fast Searching. An enormous amount of data stored in content management system as few big module as product data, slider data, personal information data, company information data, account data and another kind of data may refer to the different type of content management system and developer set. However, search specific data from all the above data type that mention, memory, and time consumed is used up. Therefore, from this paper, Boyer-Moore Horspool Algorithm is being chosen to use in content management system after comparing a few searching algorithm in research which will state in this article. The aim of this paper is to analysis few searching algorithm and choose the most suit algorithm that giving the fastest searching time consumed while searching long string data.